2012
DOI: 10.1016/j.asieco.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Disease in the post-soviet countries of Central and South-West Asia: How contagious is it?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Their products become uncompetitive due to rising real exchange rate, coupled with an influx of foreign exchange into the country (E'gert, 2009;Dobrynskaya and Turkisch, 2009;E'gert, 2012). For example, in Kazakhstan, a huge increase in oil production and a reduction in the production of many traditional products in 1990-2014 was observed (Table 4 and 5) due to the growth in the real effective rate of Tenge at the same time.…”
Section: Main Results Of the Functioning Of Such A Modelmentioning
confidence: 99%
“…Their products become uncompetitive due to rising real exchange rate, coupled with an influx of foreign exchange into the country (E'gert, 2009;Dobrynskaya and Turkisch, 2009;E'gert, 2012). For example, in Kazakhstan, a huge increase in oil production and a reduction in the production of many traditional products in 1990-2014 was observed (Table 4 and 5) due to the growth in the real effective rate of Tenge at the same time.…”
Section: Main Results Of the Functioning Of Such A Modelmentioning
confidence: 99%
“…Ultimately, massive government spending towards infrastructure projects and social programs boosted the spending effect [Hasanov, 2013]. Egert (2012) has argued that due to data issues, it is impossible to track resource movement and spending effects among the post-Soviet countries -including Azerbaijan -but concluded that increased oil prices resulted in appreciated nominal currency after certain time lags. Yun (2018) analyzed the connection between REER and manufacturing employment and between oil price and manufacturing output between 1991 and 2017 to conclude that there was significant de-industrialization and oil dependence in the Azerbaijan economy.…”
Section: Denial Of Dutch Diseasementioning
confidence: 99%
“…Concentrating the analysis of the DD phenomenon exclusively in the case of the Russian economy or comparing it with the rest of post-Soviet transition countries, several other authors (e.g., Bayulgen, 2005;Smirnova and Kulkarni, 2006;Korhonen and Juurikkala, 2007;Sosunov and Zamulin, 2007;Égert, 2012), have also investigated the presence or lack of DD problems by observing the export trend, the political factors associated with attracting FDI, and the impact of other macroeconomic monetary variables on the behaviour of the exchange rates in the Russian economy. Again, the results point to the absence of consensus regarding the presence of long-term negative effects resulting from the transmission mechanisms associated with the phenomenon of DD.…”
Section: Dutch Disease In Central and Eastern European Countries: Litmentioning
confidence: 99%
“…Large increases in oil prices have been considered responsible for economic recessions, high inflation, trade deficits, and high uncertainty, which all contribute to a decline in manufacturing growth and a loss of competitiveness following a strong real exchange rate appreciation. This leads directly to a deindustrialisation process (Caimcross, 1979;Égert and Leonard, 2008;Égert, 2012), manifested as a failure in output and employment in the manufacturing sector. Under these circumstances, most of the countries that experience a boom in natural resources tend to grow more slowly than countries without natural resources.…”
Section: Introductionmentioning
confidence: 99%